FILM DAN PESAN MORAL KEKELUARGAAN - Widia Dewi Anggraeni; Royke R. Siahainenia; Seto.Herwandito (Bajang Institute, 2022)
The occurrence of a moral crisis in adolescents in Indonesia is increasing. Film is a medium that is easily accessible by the public, so.thatpit.will make.itpeasier.for messages to be channeled properly. However, sometimes the audience only enjoys the storyline and visuals, thus ignoring the message contained in thelfilm. Thelpurpose oflthis.study ispto analyze how the moral message of kinship in the film Mulan (2020) uses Roland Barthes' semiotic theory which includes denotative, connotative and mythical meanings. Thisl.study..usedl.descriptive..qualitative.lmethod. The objectlof thisiresearch.is several.scenes inlthe.film Mulan which contain the meaning of a family moral message. Thelresults.of thislstudy canlbe concludedithat thereiis a family moral message contained in the film Mulan.